3x-4x+2x+1-3=

Simple and best practice solution for 3x-4x+2x+1-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-4x+2x+1-3= equation:


Simplifying
3x + -4x + 2x + 1 + -3 = 0

Reorder the terms:
1 + -3 + 3x + -4x + 2x = 0

Combine like terms: 1 + -3 = -2
-2 + 3x + -4x + 2x = 0

Combine like terms: 3x + -4x = -1x
-2 + -1x + 2x = 0

Combine like terms: -1x + 2x = 1x
-2 + 1x = 0

Solving
-2 + 1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 1x = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 1x = 0 + 2
1x = 0 + 2

Combine like terms: 0 + 2 = 2
1x = 2

Divide each side by '1'.
x = 2

Simplifying
x = 2

See similar equations:

| 9x^2+30x+1=0 | | 2x^2+10=98 | | 3/6x=35 | | -y=6x+4 | | (20x^2y^9z^-6/12x^-5y^-9z^-3)^-1 | | 3(3x+9)+3(3x+15)=9 | | 2(2x+8)+4=5x+4 | | X=18+-4y | | 5(3a+1)+5(a-2)= | | =-16x^2+200x+133 | | 5/20=x-7 | | 100-n=-51 | | 3x-7y-2=0 | | -5+9-6= | | -3b+4(-b+9)= | | 8a^2+224+88a=0 | | -2x-x+9+3x-2=16 | | .5x-10=22.50 | | 2(3x+1)=1(x+5)+1(t-3) | | 100-n=51 | | 4sin(2x)-2=0 | | -c+9-6= | | 4x+1-1=7 | | -q=9(q-10) | | 18d-9d-10d+-17d=-20 | | 8x-18=12+3x | | -2x-8=8-10x | | 2x-22.50=10 | | x*y*dx+(x^2-3*y)*dy=0 | | 3v+6v-3(4v-2v)= | | (1-z)(5z-6)=0 | | -.5x=8 |

Equations solver categories